Modelo de simulación para el sistema de distribución de la empresa Envía Colvanes S.A.S para la zona cuatro en la ciudad de Bogotá. - Caicedo Valencia, Jasbleidi; Vargas Cortes, Verónica Dayana (Universidad Antonio Nariño, 2023)
Simulation is the process of designing and developing a computer model of a system or process and conducting experiments on this model for the purpose of understanding its behavior or evaluating various strategies with which it can be operated. (Marquez days, Sanmartín Mendoza, & Céspedes, 2013). Based on the above, it is intended to simulate a vehicle routing system for the distribution of merchandise in Bogotá for the company Envía Colvanes S.A.S in zone four that allows optimizing the operation.